2018
DOI: 10.4067/s0718-221x2018005031901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave heating on ph and termite resistance of Pinus roxburghii wood

Abstract: This study investigated the effect of microwave treatment on wood pH and termite resistance. Pinus roxburghii heartwood was exposed to four different microwave intensities at 2450 MHz frequency for 5 minutes. Preservative impregnation, pH variation and termite resistance of microwave-treated and control specimens were studied. Wood pH decreased from 4,6 (C1) to 3,9 (T4) and preservative uptake increased (i.e., 10,4 to 21,6 kg.m-3) with increasing microwave treatment intensities. However, microwave treatment ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The Pinus sylvestris sapwood without treatment presented an average pH of 4.51, a result very close to that observed by [30], who verified a pH of 4.6 for untreated Pinus roxburghii wood.…”
Section: Phsupporting
confidence: 88%
“…The Pinus sylvestris sapwood without treatment presented an average pH of 4.51, a result very close to that observed by [30], who verified a pH of 4.6 for untreated Pinus roxburghii wood.…”
Section: Phsupporting
confidence: 88%
“…This value was lower than that of earlier reported values such as 3.58% (Zanuncio et al 2015) and 3.50% (Backlund et al 2014). Value of the pH obtained was 5.07, which was close to those of earlier reported values of 5.5 reported by Iwakiri et al (2012), but higher than the values of 3.9 to 4.6, reported by Poonia and Tripathi (2018). The above differences between the values of the present study and the ones reported earlier may be due to species variation as the species used by the latter researchers are Pinus radiata (Zanuncio et al 2015) and Pinus contorta (Backlund et al 2014).…”
Section: Particle Sizesupporting
confidence: 78%
“…Pinus roxburghii wood was studied to determine the pH and the termite resistance of samples after MW treatment using four different intensities for 5 min [57]. Poonia and Tripathi [57] remarked that no cracks or checks were found in the MW-treated samples. The MC content of the samples diminished as the MW intensity increased.…”
Section: Speciesmentioning
confidence: 99%